2021
DOI: 10.5741/gems.57.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Purple Gem Spinel from Vietnam and Afghanistan: Comparison of Trace Element Chemistry, Cause of Color, and Inclusions

Abstract: This study compares two purple gem spinel samples with regard to trace element chemistry and visible light absorption spectra, and presents the first reported example of a spinel with a saturated purple color caused predominantly by chromium and cobalt. Sample VN, from a placer deposit in the Luc Yen district of Vietnam, exhibited strong saturation, orange-red fluorescence in UV, and magnesite and graphite inclusions. Sample AF was from Badakhshan, Afghanistan, with light to medium saturation and containing ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The T Fe 2+ spin-forbidden transitions 5 E (D)→ 3 E (D) and 5 E (D)→ 3 T2 (G) are responsible for the absorption bands around ~372 nm and ~386 nm, respectively. Moreover, these absorption bands may be amplified by T Fe 2+ -M Fe 3+ ECP transitions [6,20]. Two broad bands at ~458 nm and ~476 nm may be assigned principally to spin-forbidden…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The T Fe 2+ spin-forbidden transitions 5 E (D)→ 3 E (D) and 5 E (D)→ 3 T2 (G) are responsible for the absorption bands around ~372 nm and ~386 nm, respectively. Moreover, these absorption bands may be amplified by T Fe 2+ -M Fe 3+ ECP transitions [6,20]. Two broad bands at ~458 nm and ~476 nm may be assigned principally to spin-forbidden…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
“…Two broad bands at ~458 nm and ~476 nm may be assigned principally to spin-forbidden 6 A 1g → 4 A 1g , 4 E g transitions of isolated M Fe 3+ ions, possibly intensified by ECP interactions and by spin-forbidden transitions of T Fe 2+ [6]. The absorption around ~540 nm may be caused by spin-allowed d-d transitions 3 T 1 (F)→ 3 T 2 (F) in V 3+ at the M sites or spin-allowed electronic d-d transitions 4 A 2g → 4 T 2g (F) in Cr 3+ at the M sites [6,9,20,[36][37][38][39][40][41]. (2)…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe content of purple spinel is obviously higher than that of Cr + V (Figure 17b), and Fe plays a dominant role in purple spinels. Belley et al (2021) found that the relatively low Fe content in Vietnamese purple spinels (<2437 ppm) may be the key to create attractive saturated colors [61]. The Fe content of purple spinel ranges from 1364.84 to 14,237 ppm, with an average value of 5748 ppm.…”
Section: Chromogenic Mechanism Of Spinelmentioning
confidence: 99%
“…Fluorescence is the emission of light by a substance that has absorbed light or other electromagnetic radiation, and it is utilized as a valuable tool in mineralogical sciences. There are many researches about the significant effects of fluorescence on the color appearance in minerals in the past decades, such as diamond 8 , ruby 9 , opal 10 , amber 11 , and spinel et al Natural gem-quality spinels are found all over the globe, such as Myanmar 12 , Vietnam 13 15 , Afghanistan 15 , Sri Lanka 14 , Tajikistan, and Tanzania 16 . According to the report by Vincent Pardieu, a special variety of natural spinel (typically use as “Jedi spinel” as a commercial name) with a bright neon pinkish-red color was found in Mogok and Mansin in Myanmar 12 .…”
Section: Introductionmentioning
confidence: 99%